2021
DOI: 10.1093/annweh/wxab049
|View full text |Cite
|
Sign up to set email alerts
|

Personal Solar Ultraviolet Radiation Exposure of Farmworkers: Seasonal and Anatomical Differences Suggest Prevention Measures Are Required

Abstract: Introduction Farmworkers are at risk of excess exposure to solar ultraviolet radiation (UVR) during their work activities, especially if they work in geographical areas with high ambient solar UVR levels such as in South Africa. Excess exposure to solar UVR may lead to several negative health effects such as certain cataracts and skin cancer. This study evaluated personal solar UVR exposure of a group of farmworkers to determine if they were at risk of health-related problems due to excess so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Regarding occupational factors, in the current study, those in the armed forces, construction workers, and agricultural workers showed high exceedance fractions, which is consistent with previous studies 15,16,32 . Furthermore, we were able to account for the variability within the industry.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Regarding occupational factors, in the current study, those in the armed forces, construction workers, and agricultural workers showed high exceedance fractions, which is consistent with previous studies 15,16,32 . Furthermore, we were able to account for the variability within the industry.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding occupational factors, in the current study, those in the armed forces, construction workers, and agricultural workers showed high exceedance fractions, which is consistent with previous studies. 15 , 16 , 32 Furthermore, we were able to account for the variability within the industry. For instance, we differentiated skilled agricultural workers (exceedance fraction = 0.33) and professional workers (exceedance fraction =0.14) who were all assigned to a common “agriculture, forestry, and fishery” industry (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations